2022
DOI: 10.1111/jan.15506
|View full text |Cite
|
Sign up to set email alerts
|

Recovery‐oriented mental health principles in psychiatric hospitals: How service users, family members and staff perceive the realization of practices

Abstract: Aims:The aim of the study was to describe and compare how recovery-oriented mental health principles have been realized in Finnish psychiatric hospitals from the viewpoint of different stakeholders (service users, family members and staff).Design: A multimethod research design was adopted to combine both quantitative and qualitative descriptive methods.Methods: A total of 24 focus group interviews were conducted with service users (n = 33), family members (n = 3) and staff (n = 53) on 12 psychiatric Finnish ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Facilitators were to a large extent in line with the literature and comparable with other implementation processes in (mental) health care. Examples are support from both the management of the organization and the work floor [ 43 , 44 ], momentum [ 45 ], a stable team [ 46 ], time to invest in the team spirit and work together on innovation [ 47 ], leadership [ 44 , 48 , 49 , 50 ], ambassadors [ 34 , 51 ], extra tools and trainings [ 52 , 53 ], and the exchange of knowledge and experiences with other teams [ 52 ]. This study only covered the first three years of implementation of the ART model, so other facilitators described in the literature may be relevant for the sustainability of the implementation over a longer period of time, for example, the collaboration with other partners, such as stakeholders in the community [ 54 ], the ongoing supervision of staff [ 34 , 55 ], and adequate funding [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Facilitators were to a large extent in line with the literature and comparable with other implementation processes in (mental) health care. Examples are support from both the management of the organization and the work floor [ 43 , 44 ], momentum [ 45 ], a stable team [ 46 ], time to invest in the team spirit and work together on innovation [ 47 ], leadership [ 44 , 48 , 49 , 50 ], ambassadors [ 34 , 51 ], extra tools and trainings [ 52 , 53 ], and the exchange of knowledge and experiences with other teams [ 52 ]. This study only covered the first three years of implementation of the ART model, so other facilitators described in the literature may be relevant for the sustainability of the implementation over a longer period of time, for example, the collaboration with other partners, such as stakeholders in the community [ 54 ], the ongoing supervision of staff [ 34 , 55 ], and adequate funding [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…With more positive results, a study from Finland identified differences in perceptions among staff, service users and family members about how recovery-oriented principles were realized in practice. Service users, family members and staff shared a common view that ‘dignity and respect’ had been well realized in practice on the wards, although they had opposing views regarding the principle relating to ‘recovery assessment’ (Anttila et al, 2022). In this perspective, the other study from the same country showed the high quality of Finnish mental health services, partially or fully reaching all the standards set by the WHO QualityRights Toolkit, but also pointed out areas where improvements are needed (Lantta et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Facilitators were mostly in line with literature and comparable with other implementation processes in (mental) health care. Examples are support from both the management of the organization and the work floor (Becker et al, 1998;Deane et al, 2006), a clear starting point (Aust et al, 2010), a stable team (Woltmann et al, 2008), time to invest in the team spirit and work together on innovation (McArthur et al, 2021), leadership (Anttila et al, 2022;Becker et al, 1998;Mancini et al, 2009;Whitley et al, 2009), ambassadors (Aarons et al, 2012;, extra tools and trainings (Kash et al, 2014;Shortell, 2004) and the exchange of knowledge and experiences with other teams (Shortell, 2004). This study only covered the first three years of implementation, so other relevant facilitators described in literature may be relevant for the sustainability of the implementation, for example the collaboration with other partners, such as stakeholders in the community (Markström et al, 2018), ongoing supervision of staff and adequate funding .…”
Section: Discussionmentioning
confidence: 99%